The effects of mental rotation on computational thinking. (November 2019) - Città, Giuseppe; Gentile, Manuel; Allegra, Mario; Arrigo, Marco; Conti, Daniela; Ottaviano, Simona; Reale, Francesco; Sciortino, Marinella
Abstract: Although several investigations of spatial reasoning and mental rotation skills have been conducted in research areas linked to STEM education, to the best of our knowledge, few of these studies have examined the relationship between spatial reasoning and computational thinking. Given this gap in the literature, the present study investigates the role and action of spatial reasoning, and specifically the effects of mental rotation on computational thinking within an embodied and enacted perspective. To achieve this, we carried out a study involving 92 students in five primary-school classes (1st grade - 5th grade). The findings reveal a positive correlation between computational thinking skill and mental rotation ability. Highlights: Computational thinking is a high-level cognitive process closely connected to sensorimotor factors. Complex processes underlying computational thinking emerge from concrete, situated, and action-based practices. The findings reveal a positive correlation between computational thinking skill and mental rotation ability. Gender does not influence the relationship between coding ability and mental rotation skills. This relationship is quite stable among the different school grades of primary school.